The Singapore directorship report 2014 - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2014)
Directors play an important role in the governance of firms. This reportprovides a comprehensive study of 3,670 directors on the boards of 717companies, business trusts and REITs listed on the Singapore Exchange(SGX) as at the end of 2013. This report specifically examines the structureof boards and their composition, director tenure, remuneration, meetingattendance, gender diversity and multiple directorships. It also documentscompliance with key aspects of the Singapore Code of CorporateGovernance 2012 (the Code) relating to some of these matters.